Wahhábi dalam Perspektif HUDA dan Implikasinya terhadap Kehidupan Sosial Keagamaan di Aceh - Miswar, Khairil (Tadabbur: Jurnal Peradaban Islam, 2020)
The HUDA, Himpunan Ulama Dayah Aceh (Association of Aceh Traditional Islamic Scholars) has generally viewed the Wahhabism as a heretical group. However, in practice the HUDA ulemas (Islamic scholars) have a different assessment on Wahhabi-developed teachings, either in theology or in fiqh (Islamic jurisprudence). This study examined the perceptions of the HUDA on Wahhabism and their implications for socio-religious life in Aceh. This was a qualitative study, combining library research and field research. The approach used was the sociological-phenomenological approach. Data were collected by interview and literature survey. Findings indicated that, in terms of theology, the HUDA perceived the Wahhabi movement asdeviant and heretical. In the case of fiqh, however, the Wahhabism has not followed any madhhabs (schools of thought) or mixed them. While in the socio-religious life, the Wahhabis often accused others of practicing bid‘ah (heresy) and shirk (polytheism). There were also some HUDA ulemas who considered Muhammadiyah part of the Wahhabism. The HUDA also believed that LIPIA, As-Sunnah Islamic boarding school, and Imam Shafi‘i boarding school were some educational institutions involved in spreading Wahhabism in Aceh. As Wahhabism has spread throughout Aceh, there have been resistance movements by the dayah ulema, leading to trigger people’s social movements. The study concluded that the HUDA has developed a negative perception towards the Wahhabism. As a consequence, the perception has caused hatred to arise within the community towards the Wahhabism. This also resulted in the emergence of dayah ulema’s resistance and refusal movements to the Wahhabism in Aceh.